2011
DOI: 10.1186/1471-2377-11-138
|View full text |Cite
|
Sign up to set email alerts
|

Long-term prognosis of symptomatic isolated middle cerebral artery disease in Korean stroke patients

Abstract: BackgroundThis study aimed to investigate the long-term mortality and recurrence rate of stroke in first-time stroke patients with symptomatic isolated middle cerebral artery disease (MCAD) under medical management.MethodsWe identified 141 first ever stroke patients (mean age, 64.4 ± 12.5 years; 53% male) with symptomatic isolated MCAD. MCAD was defined as significant stenosis of more than 50% or occlusion of the MCA as revealed by MR angiography. The median follow-up was 27.7 months. We determined a cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Symptomatic intracranial atherosclerotic stenosis (ICAS) is a significant independent predictor of stroke recurrence and mortality in Asian patients. 1 In China, ICAS is responsible for 42%–50% of strokes, a rate that varies based on geographic location. 2 The high rate of stroke recurrence in ICAS patients has led to a search for novel approaches to reduce the risk of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic intracranial atherosclerotic stenosis (ICAS) is a significant independent predictor of stroke recurrence and mortality in Asian patients. 1 In China, ICAS is responsible for 42%–50% of strokes, a rate that varies based on geographic location. 2 The high rate of stroke recurrence in ICAS patients has led to a search for novel approaches to reduce the risk of stroke.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus is a well-known risk factor for both small and large vessel diseases. Previous studies have identified diabetes mellitus as a risk factor for recurrent vascular events or death in patients with predominantly intracranial atherosclerosis [ 9 , 10 ]. We also identified the presence of diabetes mellitus as a potential independent potential predictor of the long-term outcome, stroke recurrence, or any-cause death.…”
Section: Discussionmentioning
confidence: 99%
“…Although the prognosis of patients with symptomatic and asymptomatic MCA stenosis has been studied previously, few studies have reported data on patients with a middle cerebral artery occlusion (MCAO). Furthermore, the previous studies have reported that the recurrence of stroke in patients with MCAO did not differ from stroke recurrence with severe MCA stenosis [ 5 , 6 , 8 , 9 ]. These studies included a very small number of patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-time outcome was evaluated using the modified Rankin Scale (mRS) (Bonita and Beaglehole 1988) applied within the first eight hours of admission (baseline) and three-month followed up. The outcome was assessed by clinical examination or using telephone interviews with the patients or their relatives (Oh et al 2011). The patients were divided in two groups: mRS < 3 was graded as favorable outcome or independence (no symptoms/mild disability) and ≥ 3 was graded as unfavorable outcome or dependence (moderate/severe disability) (Abubakar et al 2013;Uyttenboogaart et al 2005).…”
Section: Study Subjectsmentioning
confidence: 99%